Improving The Quality of Education Through Optimizing the Educational Administration System at The An-Nur Islamic Education Foundation - Aziz, Mursal; ‘Arif, Muhammad; Alwi, Muhammad Fiqri; Nugraha, Mhd Nuryansah (INJIES: Journal of Islamic Education Studies, 2024)
The success of the development process in various aspects of life cannot be separated from the contribution of administrative science to the development of all aspects of government administration in a country. Qualitative research is a research method that produces descriptive data in oral or written form about people and visible behavior. Researchers use the instructions provided by each data collection method to carry out data collection techniques. Data collection techniques include observation and document review. In this research, qualitative data analysis is carried out interactively and continues continuously until the end, so that the material is completely absorbed until it is saturated. Data reduction, data presentation, and drawing conclusions based on data and verification are all activities involved in data analysis. Quality education requires a lot of input, including teaching materials (cognitive, emotional and psychomotor), technology, school facilities, administrative support facilities and infrastructure and other resources, as well as creating a conducive environment for learning. When talking about educational outcomes, the term "quality" refers to the results or achievements achieved by a school at a certain time. Even academic success can be the result of conditions that cannot be physically possessed (intangible), such as an environment that prioritizes discipline, closeness, mutual respect, a desire to be clean, and so on.